Investigation of Measures for Sustainable Development using Sustainable Construction - Manchanayake, R.K.N.A.H.; Malkanthi, S.N.; Dassanayake, D. (University of Jaffna, 2022)
Sustainable construction practices throughout the life cycle of a project refer to minimize the adverse effect on social, environmental and economic development in a country. The present study focused on how sustainable construction practices contribute to the sustainable development of a country. 36 factors related to sustainable constructions were identified under three categories namely environmental development, social development and economic development through a comprehensive literature review. The importance of the identified factors was assessed based on the responses collected through a questionnaire. Respondents include experts in the CS2 to C5 grades construction companies. The relative importance index (RII) was used to translate the collected responses into a quantitative value. Further correlation between factors within three categories and correlation between three categories were determined through a complete SPSS analysis. With those results, it can be identified which factors need to be addressed to improve the sustainable development of a country effectively. So, project teams can get necessary actions to improve such factors to achieve sustainable development through sustainable construction practices. In addition to that factor analysis was conducted to highlight the factors that can be addressed simultaneously.
Keywords: Construction industry; Sustainable construction; Sustainable development